By members for members: How the National Art Education Association is using creative leadership to mobilize a professional community and advocate for art education. Issue 3 (1st September 2014) - Inhulsen, Dennis; Reeve, Deborah B.
The digital age and the need for visual literacy in a creative economy increase the importance of equitable and accessible art education. While Congress has recognized art education as a core component of a well-rounded public school education, students now in fact have less access to art programmes and the opportunity to pursue these programmes is less equitable in many communities. To address this paradox and to bring curricular parity, art educators must become the champions of their professional field. Grass-roots leadership cannot be taken for granted. The National Art Education Association (NAEA), once a traditional professional association, has addressed the need for organizational transformation, using creative leadership strategies to mobilize its members, to build robust communities of practice, and to create agile structures that empower art educators to become stronger leaders and advocates.